Development of a novel instrument to measure Japanese psychiatric nurses’ technological competency as caring in nursing - Takashima, Yoshiyuki; Ito, Hirokazu; Soriano, Gil P.; Yasuhara, Yuko; Osaka, Kyoko; Schoenhofer, Savina; Tanioka, Tetsuya (Belitung Raya Publisher - Belitung Raya Foundation, 2025)
Background: To effectively advance person-centered care (PCC) practice, it is important to equip healthcare providers with person-centered values and beliefs while simultaneously transforming their work environment to align with PCC. Thus, instruments to measure caring practice status in nursing competency for psychiatric-specific behavioral limitations, ethico-moral behavior, technology use, and PCC need to be developed. Objective: This study developed the Technological Competency as Caring in Psychiatric Nursing Instrument (TCCNPNI) to measure practice status and test its content and construct validity. Methods: Five different phases were followed: 1) Literature Review; 2) Operational definition of the construct and development of items; 3) Two-round Delphi method; 4) Validity measure; and 5) Reliability measure. The online survey was conducted in 2024. Results: The developed instrument comprises 22 items with a 4-factor structure: competency to practice caring and person-centered care (Factor 1); competency to recognize and respond to ethical issues in psychiatry (Factor 2); competency to utilize technology in psychiatry (Factor 3); and competence to practice care for the preservation of human dignity and shared decision making (Factor 4). Cronbach’s alpha for the entire scale was 0.864, while that for factors 1-4 was 0.911, 0.814, 0.773, and 0.64, respectively. Cumulatively, these four factors contributed 49.6% and explained nearly 50% of the total data. Item-total correlation values were 0.6 or higher among factors 1-3. However, factor 4, for which items were Q30, Q33, Q34, and Q35 (r = 0.03, 0.04, 0.21, 0.11, respectively), were inverted items and had low I-T correlation values. These low correlations suggest that these items capture different concepts. The developed TCCNPNI allows for the measurement of the practice of nursing as caring in psychiatry, the state of ethico-moral behavior, and the practice status of technological competency as caring in psychiatric nursing. Conclusion: This study demonstrated satisfactorily and efficiently evaluated the practice status of technological competency in psychiatric nurses’ caring. Measuring technological competency as caring in psychiatric nursing can be an important adjunct for in-service education in psychiatric hospitals or formalized nursing education in nursing universities.